Associations between social media usage and alcohol use among youths and young adults: findings from Understanding Society. (22nd April 2021) - Ng Fat, Linda; Cable, Noriko; Kelly, Yvonne
Abstract: Background and Aims: Given the decline in alcohol consumption and rise in technological use among young people, there is a need to investigate whether technology use might influence how young people drink. This study explores how social media use and changes in social media use over time could affect alcohol use among youths. Design: The UK Household Longitudinal Study (Understanding Society). Setting: United Kingdom. Participants: Participants aged 10–15 ( n = 4093) and 16–19 ( n = 2689) from the youth and main survey interviewed in 2011–13, and followed‐up in 2014–16 (aged 10–15 n = 2588, aged 16–19 n = 1057). Measurements: Self‐reported social media usage on an average day (no profile/non‐daily/less than an hour/1–3/4+ hours use), drinking frequency (never/one to three times/weekly) and binge drinking frequency (never/one to two/three/more than three times) in the past month. Covariates included sex, age, educational status, household income, urban/rural, number of friends and life satisfaction. Findings: Among 10–15‐year‐olds, compared with those who used social media for less than an hour, those with no profile [odds ratio (OR) = 0.41, 95% confidence interval (CI) = 0.25–0.67] and non‐daily users (OR = 0.49, 95% CI = 0.33–0.72) had a lower risk of drinking at least monthly, whereas those with 1–3 hours' use (OR = 1.44, 95% CI = 1.14–1.81) and 4+ hours' use (OR = 2.08, 1.47–2.95) had a greater risk. Among participants aged 16–19, a lower risk of binge drinking three or more times per month was found for those with no profile [relative risk ratios (RRR) = 0.29, 95% CI = 0.17–0.48] and a higher risk for those with 4+ hours' use (RRR = 1.47, 95% CI = 1.03–2.09). Longitudinally, among 10–15‐year‐olds, those who had increased their social media usage versus no change were more likely to have increased their drinking frequency (OR = 1.89, 95% CI = 1.45–2.46). Some social media use at baseline (rather than none) was predictive of increased drink and binge drinking frequency over time among youths and young adults. Conclusions: Heavier social media use was associated with more frequent alcohol consumption among young people in the United Kingdom.